SISTEM RESIRKULASI AIR OTOMATIS UNTUK PENGHEMATAN AIR BERSIH DAN ENERGI PADA BUDIDAYA IKAN NILA: The Automatic Water Recirculation System for Clean Water and Energy Saving in Tilapia Farming - Sukarno, Ragil; Ramadhan , Muhammad Fajar; Andriansyah, Farezi; Adigutama, Yudha; Syamsuir; Sampurno , Hari (Universitas Negeri Jakarta, 2024)
The acidity and turbidity of water are essential factors in tilapia farming, so it is necessary to control the acidity (pH) and turbidity (NTU) of water. This research aims to develop an automatic water recirculation system to save the use of clean water and energy consumption in tilapia fish farming using a microcontroller based on pH and turbidity (NTU) values. The research method used is experimental, starting with design and manfacture an Experimental apparatus in the form of a fish pond from a box-shaped tarpaulin, a filter system, a water circulation system consisting of pipes and a pump that has a suction power of 25 lpm, an Arduino-based microcontroller water quality controller. Tests were carried out by comparing water's pH and NTU values before and after filtering. The results showed that using a water recirculation system in a fish pond equipped with a filter system and an Arduino-based microcontroller system can significantly maintain the pH value and reduce the turbidity level (NTU). Using a recirculation system provides energy savings for pump consumption of 51.4% at a water flow rate of 15 lpm and 32.3% at a water flow rate of 25 lpm compared to conventional systems. Overall, the recirculation system provides the benefits of energy savings in pump operation, savings in water usage, and controlled water quality.